'But is it a question worth asking?' A reflective case study describing how public involvement can lead to researchers' ideas being abandoned. (31st May 2012) - Boote, Jonathan D.; Dalgleish, Mary; Freeman, Janet; Jones, Zena; Miles, Marianne; Rodgers, Helen
Abstract Background It is good practice for the public to be involved in developing research ideas into grant applications. Some positive accounts of this process have been published, but little is known about when their reactions are negative and when researchers' ideas are abandoned. Objective To present a case study account of when an academic‐led idea for funding was not supported by stroke survivors and carers who were asked to contribute to its development, together with a reflection on the implications of the case from all the stakeholders involved. Design A reflective case study of a research idea, developed by an academic researcher, on which stakeholders were consulted. Participants University researchers, clinicians, public involvement managers, and stroke survivors and carers from the NIHR's Stroke Research Network. Findings Although the idea met with the approval of health professionals, who were keen to develop it into a funding bid, the stroke survivors and carers did not think the idea worth pursuing. This lack of patient and carer support led to the idea being abandoned. Reflecting on this, those involved in the consultation believed that the savings accrued from abandoning the idea, in terms of ensuring that public money is not wasted, should be seen as an important benefit of public involvement in the research process. Conclusion Little is known about the role of the public in the abandonment of research ideas. We recommend that further research is undertaken into this important contribution that patients and the public can make to health research.